Use of an intraoperative wound protector to prevent surgical‐site infection after pancreatoduodenectomy: randomized clinical trial. Issue 9 (12th March 2020) - De Pastena, M.; Marchegiani, G.; Paiella, S.; Fontana, M.; Esposito, A.; Casetti, L.; Secchettin, E.; Manzini, G.; Bassi, C.; Salvia, R.
Abstract : Background: Surgical‐site infection (SSI) increases treatment costs, duration of hospital stay and readmission rate after pancreatic surgery. This study aimed to assess whether a wound protector could reduce the risk of superficial incisional SSI after pancreatoduodenectomy. Methods: This RCT included patients undergoing pancreatoduodenectomy at Verona University Hospital, between 2017 and 2018. The experimental group had a dual‐ring wound protector, whereas the control group had standard surgical drapes. The groups were stratified by preoperative biliary stent placement. The primary outcome was the overall rate of superficial SSI. Results: An interim analysis was conducted after 212 patients had been enrolled; 22 patients (10·4 per cent) were excluded owing to inability to complete the pancreatoduodenectomy, or the need for postoperative reintervention. Some 94 patients (49·5 per cent) had a wound protector and 96 (50·5 per cent) had standard drapes. There were no differences between groups in demographics, or in intraoperative findings, pathological data or surgical outcomes. The overall superficial SSI rate was 7·4 per cent, which did not differ between groups (7 per cent in each group; P  = 0·585). Subanalysis of patients with a preoperative biliary stent showed a similar outcome (superficial SSI rate 9 versus 8 per cent with wound protector versus surgical drapes respectively; P  = 0·536). The trial was stopped prematurely on the grounds of futility. Conclusion: Use of a wound protector did not reduce the rate of superficial SSI after pancreatoduodenectomy. Registration number: NCT03820648 (http://www.clinicaltrials.gov ). Abstract : This RCT assessed whether a wound protector could reduce the risk of superficial incisional surgical‐site infection (SSI) in patients undergoing pancreatoduodenectomy. In a high‐volume centre, use of a wound protector alone did not reduce the superficial SSI rate. It could be introduced in a wider implementation programme, which should be directed at local issues in the reduction of infectious complications. Likely ineffective Abstract : Antecedentes: La infección de la herida quirúrgica ( surgical‐site infection, SSI), especialmente de la incisión, aumenta sobremanera los costes del tratamiento, la duración de la estancia y la tasa de reingresos en la cirugía de páncreas. En los últimos años se han introducido los protectores de las heridas ( wound protectors, WP) con la intención de reducir la tasa de SSI. Este estudio tuvo como objetivo evaluar si un WP podría reducir la incidencia de la SSI superficial de la incisión ( superficial incisional surgical‐site infection, SI‐SSI) en pacientes sometidos a duodenopancreatectomía cefálica ( pancreaticoduodenectomy, PD). Métodos: Ensayo aleatorizado controlado en el que se incluyeron los pacientes a los que se realizó una PD en la Universidad de Verona entre 2017 y 2018. En el grupo experimental se utilizó un WP de doble anillo, mientras que el grupo control se utilizaron tallas quirúrgicas convencionales ( standard drape, SD). Los grupos se estratificaron también según la colocación preoperatoria de una prótesis biliar. Resultados: Se incluyeron 212 pacientes, de los que 22 (10%) abandonaron el estudio debido a la imposibilidad de realizar la DP o a la necesidad de una reintervención durante el curso postoperatorio. Los pacientes se dividieron en 94 (49%) en el grupo WP y 96 (51%) en el grupo SD. No se detectaron diferencias entre grupos en cuanto a las variables demográficas y a los resultados intraoperatorios, patológicos o quirúrgicos. La tasa global de SI‐SSI fue del 7, 4%, que no difirió entre los grupos (WP 7, 5% versus SD 7, 3%, P = 0, 585). Teniendo en cuenta los resultados descritos, se cumplieron los criterios de futilidad del análisis y el ensayo se interrumpió prematuramente. Conclusión: En el entorno de un centro de alto volumen, la WP por si sola no redujo la tasa de SI‐SSI. Cabría plantear su utilización dentro de un programa multimodal, que debería incluir un replanteamiento interno de la institución encaminado a la reducción de complicaciones infecciosas.